Morphology and morphometry of proximal dry radii in south coastal population - Rajasree, Gali; Sucharitha, Todimaldinnae; Karuppiah, Devi Sankar; Hema, Lattupalli (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
Knowledge of the size and shape of radial head is essential for construction of radialhead prosthesis. Further, the measurements of bicipital tuberosity and its angularrelationship to radial head are significant in surgical techniques, like in thereconstruction of biceps tendon. Even the morphometry of the distal radius is significantin numerous clinical orthopedic situations such as reduction of distal radius fracturesand in the design of distal radius prosthesis. So, the aim of the study was to determinethe morphometric parameters of proximal and distal radius in dry adult Indian radius.